AN ANALYSIS OF TEACHERS’ CHALLENGES IN IMPLEMENTING THE MERDEKA CURRICULUM POLICY IN THE TEACHING PROCESS AT SDN 158 PALEMBANG - Mahesa, Khovipa; Azzahra, Luthfiah; Azzahra, Fatimah; Sari, Yunita; Afriantoni (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the challenges faced by teachers in implementing the Merdeka Curriculum policy in the teaching process at SDN 158 Palembang. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that teachers encounter various obstacles, including differences in understanding of the Merdeka Curriculum concepts, limited learning resources and technological facilities, increased workload, and the need for ongoing training and mentoring. Additionally, students’ adaptation to the new learning approach and the lack of collaboration among teachers are also significant challenges. Support from the school administration is considered essential in ensuring the successful implementation of this curriculum. The study recommends enhancing practical training, providing adequate learning materials, strengthening digital literacy, and establishing a consistent mentoring system to ensure the effective implementation of the Merdeka Curriculum at the elementary school level. Penelitian ini bertujuan untuk menganalisis tantangan yang dihadapi oleh guru dalam menerapkan kebijakan Kurikulum Merdeka pada proses pembelajaran di SDN 158 Palembang. Dengan pendekatan kualitatif jenis studi kasus, data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian mengungkapkan bahwa guru menghadapi sejumlah kendala, antara lain perbedaan pemahaman terhadap konsep Kurikulum Merdeka, keterbatasan sumber belajar dan sarana teknologi, peningkatan beban kerja, serta kebutuhan akan pelatihan dan pendampingan yang berkelanjutan. Selain itu, adaptasi siswa terhadap pendekatan pembelajaran yang baru dan kurangnya kolaborasi antarguru juga menjadi tantangan yang signifikan. Dukungan dari pihak sekolah dinilai sangat krusial dalam menunjang keberhasilan implementasi kurikulum ini. Penelitian ini merekomendasikan peningkatan pelatihan praktis, penyediaan sumber belajar yang memadai, penguatan literasi digital, serta sistem pendampingan yang konsisten untuk memastikan efektivitas Kurikulum Merdeka di tingkat sekolah dasar.